A systematic review of social media acceptance from the perspective of educational and information systems theories and models - Al-Qaysi, Noor; Norhisham, Mohamad-Nordin; Al-Emran, Mostafa (SAGE Publications Inc., 2020)
The study of social media acceptance and adoption is not a new research topic. However, the analysis of the educational and information systems (IS) theories/models that are used to examine the social media acceptance and adoption is considered an important research direction. To examine these theories/models and provide researchers with a clear vision of this research topic, we should be aware of the leading educational and IS theories/models used in this line of research. To this end, this systematic review retrieved and analyzed 2,382 articles. The retrieved articles were then critically examined to meet the inclusion and exclusion criteria, in which 122 articles published between 2009 and 2018 were eventually selected for further critical analysis. The main findings indicated that the uses and gratifications theory (U&G) and the social constructivism theory were considered the most widely used educational theories in social media. Besides, the technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT) were considered the most extensively used IS models in studying the social media acceptance and adoption. These results afford a better understanding of social media studies related to the educational and IS theories/models and form a constructive reference for future research.